2009
DOI: 10.1002/cjce.20154
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐up study of spouted beds using computational fluid dynamics

Abstract: This work presents a numerical study of the hydrodynamic of spouted beds using computational fluid dynamics (CFD) simulation. Scaling relationships proposed by He et al. [He et al., Chem. Eng. Sci. 1997;52:329-339] for spouted bed systems based on similitude method are numerically investigated using CFD simulation. In the present work it is verified that the spouted bed scale-up relationships of He et al. [He et al., Chem. Eng. Sci. 1997;52:329-339] produce good numerical results when all of the scale-up re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…A scale-up relationship for spouted beds was proposed by He et al [197]; Bettega and colleagues [235] verified its validity with a 2D model, confirming that when the scaling relationships were not satisfied, the hydrodynamics of the beds was severely hindered.…”
Section: Particle Mixingmentioning
confidence: 93%
“…A scale-up relationship for spouted beds was proposed by He et al [197]; Bettega and colleagues [235] verified its validity with a 2D model, confirming that when the scaling relationships were not satisfied, the hydrodynamics of the beds was severely hindered.…”
Section: Particle Mixingmentioning
confidence: 93%
“…According to their numerical study, the solid‐phase dynamic behaviour tends to disturb the flow inside the vessel; even the friction between solid phase and flat wall was negligible. In another work, Bettega et al investigated scaling relationships proposed by He et al for spouted bed systems based on similitude method using CFD simulation. They found that if all of the scale‐up relations are fulfilled, numerical simulation shows good results.…”
Section: Introductionmentioning
confidence: 99%
“…The authors devised good predictions using this model. Many other researchers have adopted this kind of approach in the simulations of spouted beds, obtaining relevant information about their fluid dynamics …”
Section: Introductionmentioning
confidence: 99%